The Effect Of Work Discipline And Compensation On Employee Performance Productions Department Cv. Jasa Karya Nusantara Banjar City - Fahrani, Daffa Annasya; Barlian, Barin; Asyiah, Ai Kusmiati (Universitas Dehasen Bengkulu, 2023)
This study aims to determine the effect simultaneously and partially between Work Discipline and Compensation on Employee Performance at CV. Archipelagic Services for the City of Banjar. The research method used is a survey method with a quantitative approach. The sampling technique used the saturated sample method with a total sample of 50 people. Data collection techniques using online and offline questionnaires. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26. The results of the study show that work discipline and compensation simultaneously have a significant effect on employee performance. Partially work discipline has a significant effect on employee performance. Partially, compensation has a significant effect on employee performance.